Antioxidative and anti-inflammatory effects of vitamin C on the liver of laying hens under chronic heat stress - Du, Jun; Shi, Yan; Zhou, Changming; Guo, Lianying; Hu, Ruiming; Huang, Cheng; Hu, Guoliang; Gao, Xiaona; Guo, Xiaoquan (Frontiers in Veterinary Science, 2022)
In this study, we investigated the therapeutic effect and mechanism of action of vitamin C on chronic heat stress (CHS)-induced liver oxidative damage and inflammation in laying hens. The thermoneutral control group (TN group) was kept at a constant temperature of 22 ± 1 °C, while the chronic heat stress group (CHS group) and the vitamin C supplemented group (HSV group) were exposed to heat stress (HS) (36 ± 1 °C, 8 h/d). The TN and HS groups were fed the basic diet at will, and the HSV group was supplemented with 300 mg/kg of vitamin C on top of the basic diet. The experimental results showed a significant improvement in body weight and feed intake in the HSV group compared to the HS group. A significantly lower pH and higher HCO3- and PCO2 levels were observed in the HSV group compared to the CHS group. As laying hens were supplemented with vitamin C, serum malondialdehyde (MDA) level was declined, superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities were increased, and total antioxidant capacity (T-AOC) was increased. Further, CHS induced an increase in the expression of inflammation-related genes and a decrease in the expression of antioxidant-related genes. In contrast, the addition of vitamin C reversed the effects of CHS, resulting in an increase in the expression of antioxidant-related genes and a decrease in the expression of inflammation-related genes. In conclusion, vitamin C can effectively alleviate CHS-induced acid-base imbalance in body fluids of laying hens and the oxidative damage and inflammatory response caused to the liver. Therefore, vitamin C can be used clinically as an effective drug to alleviate chronic heat stress in laying hens. This experiment provides clinical evidence and theoretical basis for the use of vitamin C as an effective drug to alleviate chronic heat stress in laying hens.